Rainfall, poverty and crime in 19th Century Germany - Halvor Mehlum; Edward Miguel; Ragnar Torvik (University of Oslo, Department of Economics, 2004)
We estimate the impact of poverty on crime in 19th century Bavaria, Germany. Rainfall is used as an instrumental variable for the price of rye to address identification problems found in the existing literature. The rye price was a major determinant of the cost of living and poverty during this period. The rye price has a positive and statistically significant effect on property crime: a one standard deviation increase in the rye price increased property crime by a moderate 8 percent, a result similar to recent findings from the contemporary U.S. This result is robust to another poverty measure (the real wage), and when we restrict attention to lagged rainfall measures as instruments – ruling out some possible violations of the exclusion restriction. OLS estimates are twice as large as instrumental variable estimates. Higher rye prices lead to significantly less violent crime, though, and we argue that higher beer prices (caused by higher rye prices) are a likely explanation. We discuss implications for economic theories of crime, and for public policy in less developed countries today.
Keywords: N93; 330; Poverty; Crime; Rainfall; Germany; Kriminalität; Armut; Roggen; Getreidepreis; Bayern; Wetter